IMPLEMENTASI MANAJEMEN HUMAS DALAM MENINGKATKAN CITRA POSITIF DI LEMBAGA PEMASYARAKATAN KELAS IIB SLAWI - Ahmad, Syaerozi; Pangestuti, Naniek (Journal of Management Small and Medium Enterprises (SMEs), 2024)
Public relations management plays a strategic role in building positive relationships between institutions and stakeholders, such as the community, media, and government. This research was conducted to understand how public relations management is implemented at Slawi Correctional Facility and how concrete steps in communication can affect the image of the institution. This article uses a descriptive qualitative approach in the research and discussion. The results show that the public relations team of Slawi Correctional Facility has made real efforts in designing and implementing public relations management strategies. The results show that Slawi Correctional Facility is committed to planning an effective communication strategy. They actively use various media channels, including mass media and social media, to communicate positive programs and information to the community. Obstacles such as the lack of adequate public relations infrastructure, lack of teamwork, and overlapping tasks are challenges faced. However, Slawi prison has shown initiative in overcoming these obstacles. Collaboration within the public relations team and good internal communication among team members are also important factors in the success of communication efforts. In addition, a data-driven approach is also used to measure community satisfaction with the programs and services provided by Lapas Slawi. Keywords: Public Relations Management; Career Development; Correctional Institution